2021
DOI: 10.15405/epsbs.2021.04.28
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Potential And Socio-Economic Development Of The Region

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Noncommercial 4.0 Unported License, permitting all non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…Therefore, this method is better for the evaluation of economic development after intervention. Some scholars analyzed 102 sports industries, and the results showed that the choice of improving the development mode of sports industry needs to refer to the economic growth of the industry, and the analysis time has little impact on the analysis results, which is consistent with the research results of this paper [ 18 ]. Some scholars have proposed that the economic scale of 20–30 trillion should be integrated by early assessment and step-by-step extension.…”
Section: Discussionsupporting
confidence: 85%
“…Therefore, this method is better for the evaluation of economic development after intervention. Some scholars analyzed 102 sports industries, and the results showed that the choice of improving the development mode of sports industry needs to refer to the economic growth of the industry, and the analysis time has little impact on the analysis results, which is consistent with the research results of this paper [ 18 ]. Some scholars have proposed that the economic scale of 20–30 trillion should be integrated by early assessment and step-by-step extension.…”
Section: Discussionsupporting
confidence: 85%